Resposta de pastagem de grama-tapete no período subsequente à adubação com dejeto líquido de suíno - Kottwitz, Daiane Carla (2012)
The dry matter (DM) production, apparent residual effect, botanical and chemical composition of a carpet grass pasture were evaluated after successive pig slurry (PS) applications. On the average of the two years before the first cut, the pasture received 0, 51, 102, 153, 204 and 255 m3 of PS/ha and a treatment with 625 kg of ammonium nitrate/ha. The pasture was cut four times in the period of 412 days after the last nitrogen fertilizer applications. A positive and linear effect (8 kg of DM/m3/ha) in the yield was verified in response to the PS fertilization. The apparent residual effect of PS ranged from 302 kg of DM/ha (51 m3) to 2,020 kg of DM/ha (255 m3), and of the ammonium nitrate was 939 kg of DM/ha. There was significant reduction in the legume participation in the forage in response to the pig slurry and ammonium nitrate fertilization. The clustering analysis showed the formation of two groups: group 1 was formed by the treatment without nitrogen fertilization, and group 2 consisted of the other treatments. The group 2 showed a small contribution of legumes (1.7%) and dicotyledonous (2.5%), and group 1 was characterized by a higher contribution of these components, 19.0% and 20.2%, respectively. The chemical composition was not affected by treatments, with average of 10.8% of crude protein, 39.2% of acid detergent fiber, and 74.0% of neutral detergent fiber.